The influence of different training load quantification methods on the fitness-fatigue model - Vermeire, K. M.; Van de Casteele, F.; Gosseries, M.; Bourgois, J. G.; Ghijs, M.; Boone, J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Numerous methods exist to quantify training load (TL). However, the relationship with performance is not fully understood. Therefore the purpose of this study was to investigate the influence of the existing TL quantification methods on performance modeling and the outcome parameters of the fitness-fatigue model.